Effects of the Relaxation of Upwelling‐Favorable Winds on the Diurnal and Semidiurnal Water Temperature Fluctuations in the Santa Barbara Channel, California. Issue 10 (20th October 2017) - Aristizábal, María F.; Fewings, Melanie R.; Washburn, Libe
Abstract: In the Santa Barbara Channel, California, and around the Northern Channel Islands, water temperature fluctuations in the diurnal and semidiurnal frequency bands are intermittent, with amplitudes that vary on time scales of days to weeks. The cause of this intermittency is not well understood. We studied the effects of the barotropic tide, vertical stratification, propagation of coastal‐trapped waves, regional wind relaxations, and diurnal‐band winds on the intermittency of the temperature fluctuations during 1992–2015. We used temperature data from 43 moorings in 10–200 m water depth and wind data from two buoys and one land station. Subtidal‐frequency changes in vertical stratification explain 20–40% of the intermittency in diurnal and semidiurnal temperature fluctuations at time scales of days to weeks. Along the mainland north of Point Conception and at the Northern Channel Islands, the relaxation of upwelling‐favorable winds substantially increases vertical stratification, accounting for up to 55% of the subtidal‐frequency variability in stratification. As a result of the enhanced stratification, wind relaxations enhance the diurnal and semidiurnal temperature fluctuations at those sites, even though the diurnal‐band wind forcing decreases during wind relaxation. A linear model where the background stratification is advected vertically explains a substantial fraction of the temperature fluctuations at most sites. The increase of vertical stratification and subsequent increase in diurnal and semidiurnal temperature fluctuations during wind relaxation is a mechanism that can supply nutrients to the euphotic zone and kelp forests in the Channel in summer when upwelling is weak. Key Points: Changes in background vertical stratification account for 20%–40% of the intermittency in temperature fluctuations Winds relaxations increase vertical stratification at the Northern Channel Islands Wind relaxations enhance the tidal‐band temperature fluctuations at the Northern Channel Islands